Ceramics international. ([Ceramurgica], 1981)
"Ceramics International primarily deals with the fundamental aspects of ceramic science and their application to the development of improved ceramic materials. The journal particularly encourages papers that show how ceramic science can be used to improve the quality, reliability and performance of ceramics through the development of advanced materials and manufacturing techniques."